Pengaruh Beban Pajak Tangguhan, Perencanaan Pajak Dan Modal Intelektual Terhadap Nilai Perusahaan - Widiyati, Dian; Lukmana, Fariz (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This study aims to determine the effect of deferred tax burden, tax planning, and intellectual capital on company value in sector consumer non-cyclicals sub sector food and beverage companies listed on the Indonesia Stock Exchange in 2018-2022. Based on the number of samples in this study, as many as 41 companies obtained through the purposive sampling method were the object of research in accordance with the criteria. A sample of 205 data was obtained. This study used regression analysis of panel data, using Eviews 9. Based on the results of the analysis tested, it shows that (1) Deferred tax burden, tax planning and intellectual capital simultaneously affect the value of the company. (2) Deferred tax burden has no effect on company value, (3) Tax planning has no effect on company value, (4) Intellectual capital has a negative and significant effect on company value.